Smart casual : the transformation of gourmet restaurant style in America - Pearlman, Alison (Chicago ; London : University of Chicago Press, 2013)
Explores the evolution of gourmet restaurant style in recent decades, which has led to an increasing informality in restaurant design, and examines what these changes say about current attitudes toward taste.
When fine dining met casual dining -- New shapers of trends and taste -- Exhibition kitchens and the theater of manual labor -- Gourmet plays on common food faves.
Includes bibliographical references (pages 159-196) and index.
Keywords: Gastronomy -- United States -- History -- 20th century; Gastronomy -- United States -- History -- 21st century; Restaurants -- United States -- History -- 20th century; Restaurants -- United States -- History -- 21st century; Gastronomy; Restaurants; United States; 1900-2099; History